The impact of 'grounds' on abortion-related outcomes: a synthesis of legal and health evidence - Fiona de Londras; Amanda Cleeve; Maria I. Rodriguez; Antonella F. Lavelanet (BMC, 2022)
Abstract Where abortion is legal, it is often regulated through a grounds-based approach. A grounds-based approach to abortion provision occurs when law and policy provide that lawful abortion may be provided only where a person who wishes to have an abortion satisfies stipulated 'grounds', sometimes described as 'exceptions' or 'exceptional grounds'. Grounds-based approaches to abortion are, prima facie, restrictive as they limit access to abortion based on factors extraneous to the preferences of the pregnant person. International human rights law specifies that abortion must be available (and not 'merely' lawful) where the life or health of the pregnant woman or girl is at risk, or where carrying a pregnancy to term would cause her substantial pain or suffering, including but not limited to situations where the pregnancy is the result of rape or incest or the pregnancy is not viable. However, international human rights law does not specify a grounds-based approach as the way to give effect to this requirement. The aim of this review is to address knowledge gaps related to the health and non-health outcomes plausibly related to the effects of a grounds-based approach to abortion regulation. The evidence from this review shows that grounds have negative implications for access to quality abortion and for the human rights of pregnant people. Further, it shows that grounds-based approaches are insufficient to meet states' human rights obligations. The evidence presented in this review thus suggests that enabling access to abortion on request would be more rights-enhancing than grounds-based approaches to abortion regulation.